Impact of Environmentally Relevant Concentrations of Glyphosate and 2,4-D Commercial Formulations on Nostoc sp. N1 and Oryza sativa L. Rice Seedlings - Tansay, Suwakan; Issakul, Kritchaya; Ngearnpat, Neti; Chunhachart, Orawan; Thuptimdang, Pumis (Frontiers in Sustainable Food Systems, 2021)
Wide applications of glyphosate and 2,4-dichlorophenoxyacetic acid (2,4-D) in rice paddy fields could lead to their residues in environment, posing adverse effects on rice growth and primary producers in the rice ecosystem. This research aims to determine the effects of environmentally relevant concentrations of glyphosate and 2,4-D commercial formulations on Nostoc sp. N1 and rice seedlings. The effects of herbicides on Nostoc sp. N1 were measured from the growth and acute toxicity. The germination and growth were used to determine the effects of herbicides on rice seedlings by measuring their physical and biochemical characteristics. Results showed that while glyphosate had higher toxicity than 2,4-D, both herbicides could stimulate the growth of Nostoc sp. N1 as indicated by their increase in biomass and chlorophyll a content. In Petri dish experiments, Nostoc sp. N1 cells not only promoted the germination of rice seedlings when added alone, but they also alleviate the toxicity of both herbicides to the rice seedlings. In pot experiments, the addition of Nostoc sp. N1 cells combined with herbicides promoted the biochemical characteristics of the rice seedlings by increasing the total chlorophyll, carotenoid and total amino acid content. Our results suggested that environmentally relevant concentrations of glyphosate and 2,4-D formulations should not pose any adverse effects on Nostoc sp. N1. Also, with their toxicity-mitigating and growth-promoting effects on rice seedlings, Nostoc sp. N1 cells could be applied in the alleviation of herbicide residue toxicity in paddy fields.